Exploration and practice of AI-empowered smart campus - SU Xiaoming; ZHANG Siyu; JIANG Kaida (Tongxin xuebao)
According to the application and practice of generative AI technologies in smart campus development, focusing on the campus AI Hub—a smart application integration platform designed for higher education, two core functionalities of the campus AI Hub, such as general application services and scenario-based solutions were highlighted. General application services included tools like intelligent translation and reading assistants, enhancing daily learning and work efficiency. Scenario-based solutions address specific needed in teaching, research, and management through customized intelligent systems. The technical architecture featured a three-layer design, such as the foundational model layer leverages open-source large language models, the development platform layer enhances system scalability, and the application service layer integrates AI tools and optimizes processes. Key technologies such as data structure transformation, visualization, and intelligent search were applied in scenario-based solutions. An open-source, co-constructed development model for the campus AI Hub was proposed, offering a scalable approach that supports smart campus transformation and contributes to digitalizing higher education.